Ixodes ricinus ticks have a functional association with Midichloria mitochondrii - Guizzo, Melina Garcia; Hatalová, Tereza; Frantová, Helena; Zurek, Ludek; Kopáček, Petr; Perner, Jan (Frontiers in Cellular and Infection Microbiology, 2023)
In addition to being vectors of pathogenic bacteria, ticks also harbour intracellular bacteria that associate with ticks over generations, aka symbionts. The biological significance of such bacterial symbiosis has been described in several tick species but its function in Ixodes ricinus is not understood. We have previously shown that I. ricinus ticks are primarily inhabited by a single species of symbiont, Midichloria mitochondrii, an intracellular bacterium that resides and reproduces mainly in the mitochondria of ovaries of fully engorged I. ricinus females. To study the functional integration of M. mitochondrii into the biology of I. ricinus, an M. mitochondrii-depleted model of I. ricinus ticks was sought. Various techniques have been described in the literature to achieve dysbiosed or apo-symbiotic ticks with various degrees of success. To address the lack of a standardised experimental procedure for the production of apo-symbiotic ticks, we present here an approach utilising the ex vivo membrane blood feeding system. In order to deplete M. mitochondrii from ovaries, we supplemented dietary blood with tetracycline. We noted, however, that the use of tetracycline caused immediate toxicity in ticks, caused by impairment of mitochondrial proteosynthesis. To overcome the tetracycline-mediated off-target effect, we established a protocol that leads to the production of an apo-symbiotic strain of I. ricinus, which can be sustained in subsequent generations. In two generations following tetracycline administration and tetracycline-mediated symbiont reduction, M. mitochondrii was gradually eliminated from the lineage. Larvae hatched from eggs laid by such M. mitochondrii-free females repeatedly performed poorly during blood-feeding, while the nymphs and adults performed similarly to controls. These data indicate that M. mitochondrii represents an integral component of tick ovarian tissue, and when absent, results in the formation of substandard larvae with reduced capacity to blood-feed.